How does team reflexivity affect new generation employee cooperative behavior in China? A cross-level moderated mediation model - Li, Yuanrong; Li, Hong; Xiao, Ya (Frontiers in Psychology, 2025)
IntroductionEmployee cooperative behavior is crucial for enterprises navigating uncertainty in the rapidly evolving digital era. Drawing on social information processing theory, this study examines the impact of team reflexivity on employee cooperative behavior, with a focus on the mediating role of organizational trust and the moderating role of employee involvement climate.MethodsA cross-level moderated mediation model was developed and tested using survey data from 412 employees across 84 project teams in China. Hierarchical linear modeling (HLM) was employed to analyze the proposed relationships.ResultsThe findings reveal that: (1) Team reflexivity significantly enhances employee cooperative behavior. (2) Organizational trust mediates the relationship between team reflexivity and employee cooperative behavior. (3) Employee involvement climate moderates the indirect effect, such that the mediation effect of organizational trust is stronger in teams with a higher level of employee involvement.DiscussionThese results contribute to the understanding of how team reflexivity fosters cooperation among employees, highlighting the critical role of trust and the influence of organizational climate. The study provides theoretical and practical implications for fostering teamwork and trust in dynamic work environments.